154 Overtriage in Patients With Complicated Mild Traumatic Brain Injury: A Socioeconomic Analysis of 1447 Hospitalizations. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Dengler, Bradley; Chick, Robert C; Plaza-Wuthrich, Sonia; Muir, Mark; Bartanusz, Viktor
Abstract: INTRODUCTION: Transfer of stable patients who might otherwise be safely observed at a community hospital adds to the ever-increasing cost of healthcare in the United States. This study aims to show that overtriage of complicated mild traumatic brain injury (mTBI) patients leads to substantial costs to a healthcare system. Secondary outcomes are predictors of overtriage and transfer times. METHODS: A 9-yr retrospective analysis of patients admitted to our tertiary care center who had mTBI with evidence of intracranial hemorrhage on computed tomography scan. Patients were dichotomized based on their mode of transfer (helicopter vs ambulance) and admission status (primary admission vs secondary admission). Secondary overtriage was defined as patients with an injury severity score less than 15, no surgical interventions performed, and hospital stay less than 48 h. Charges were calculated for each cohort, and multivariate linear regression analysis was used to determine predictors of overtriage. RESULTS: A total of 1447 patients met the inclusion criteria for this study. A total of 115 patients met the criteria for secondary overtriage. Secondary overtriaged patients are younger (median: 41 yr vs 60.5 yr, P < .001), had lower ISS (9 vs 16, P < .001), had a shorter hospital stay (1 d vs 3 d, P < .001) and a shorter intensive care unit stay ( P < .001), had lower proportion of comorbidities (38.9% vs 58.0%, P < .001) and complications (0.9% vs 7.2%, P < .001). Secondary overtriaged patients had a higher chance of being discharged home and an average transfer time of 51 min. Lack of insurance was a major predictor of overtriage. Secondary overtriaged patients had an average cost of 13 294. CONCLUSION: Significant overtriage of complicated mTBI patients leads to a cost of approximately 13 000 per patient. Eliminating these transfers is another way to save on healthcare costs.